Associated factors with hemoptys in patients with pulmonary tuberculosis at Dos de Mayo National Hospital, Lima - Peru - Condor, Briam Benito (2021)
Objectives. To determine the factors associated with hemoptysis in patients with pulmonary tuberculosis admitted at Dos de Mayo National Hospital. Methods. Analytical study of cases and controls. Patients from the tuberculosis program at Dos de Mayo National Hospital, Lima- Peru, were selected. The cases were patients with pulmonary tuberculosis with hemoptysis, and controls pulmonary tuberculosis without hemoptysis. Epidemiological, clinical and laboratory variables were studied. SPSS 24 software is used. Frequency, central trend and dispersion measurements were determined, as well as odds ratios with their respective confidence intervals at 95%, the value of p<0,05 was considered statistically significant. Results. Tuberculosis hemoptysis account for 5,8% of all patients with pulmonary tuberculosis, 80% occurred in males under 60 years old. 70% of cases had a history of alcoholic habits (OR: 2,5 CI: 1,2-5,5); 24% exposure to biomass burning (OR: 4,9 CI: 1,7-14); 66% had chest pain (OR: 3,3 IC: 1,6-6,7); tomographic alterations were present in 88% of cases (OR: 24,5 IC: 9,2-64,8); however, no variations in the coagulation profile were found. Death from hemoptysis in hospitalized patients with pulmonary tuberculosis was 20,22%. Conclusions. Chronic alcoholism and tomographic evidence of bronchiectasis were associated with hemoptysis in patients hospitalized for pulmonary tuberculosis with positive smear microscopy.